No time to die: Comparative study on preservation protocols for anaerobic fungi - Vinzelj, Julia; Joshi, Akshay; Young, Diana; Begovic, Ljubica; Peer, Nico; Mosberger, Lona; Luedi, Katharina Cécile Schmid; Insam, Heribert; Flad, Veronika; Nagler, Magdalena; Podmirseg, Sabine Marie (Frontiers in Microbiology, 2022)
Anaerobic fungi (AF, phylum Neocallimastigomycota) are best known for their ability to anaerobically degrade recalcitrant lignocellulosic biomass through mechanic and enzymatic means. While their biotechnological potential is well-recognized, applied research on AF is still hampered by the time-consuming and cost-intensive laboratory routines required to isolate, maintain, and preserve AF cultures. Reliable long-term preservation of specific AF strains would aid basic as well as applied research, but commonly used laboratory protocols for AF preservation can show erratic survival rates and usually exhibit only moderate resuscitation success for up to one or two years after preservation. To address both, the variability, and the preservation issues, we have set up a cross-laboratory, year-long study. We tested five different protocols for the preservation of AF. The experiments were performed at three different laboratories (Austria, Germany, Switzerland) with the same three morphologically distinct AF isolates (Anaeromyces mucronatus, Caeocmyces sp., and Neocallimastix cameroonii) living in stable co-culture with their naturally occurring, syntrophic methanogens. We could show that handling greatly contributes to the variability of results, especially in A. mucronatus. Cryopreservation of (mature) biomass in liquid nitrogen had the highest overall survival rates (85% to 100%, depending on the strain and laboratory). Additionally, preservation on agar at 39°C had surprisingly high survival rates for up to 9 months, if pieces of agar containing mature AF thalli were resuscitated. This low-cost, low-effort method could replace consecutive batch cultivation for periods of up to 6 months, while long-term preservation is best done by cryopreservation in liquid nitrogen. Regardless of the method, however, preserving several replicates (> three) of the same strain is highly advisable.